COVID-19 pandemic: the impact on E-commerce and consumer behavior in Pakistan - Ismail, Kamarulzaman; Jantan, Amer Hamzah; Muhammad Irfan; Naveed, Rana Tahir; Ahmed, Shakeel (Penerbit UnIPSAS, 2022)
The study is aimed at identifying the effects of COVID-19 on e-commerce businesses to gain a better understanding of how to sustain and improve the business in a hard-hit economic situation. Coronavirus is a very harmful virus, and it spreads very fast from human to human. The virus is fatal and brings many people to death in Pakistan. So, business communication is badly affected. Consequently, business transactions decreased so as economic growth. The survey research is used to collect the data via adopted scales from employees. The findings show that COVID-19 has brought a negative impact on e-commerce businesses. On the other hand, buying behaviour has a significant relationship with e-commerce. It has affected all kinds of businesses, including the SMS sector as well as online businesses.